RANCANG BANGUN SISTEM INFORMASI STANDAR HARGA BARANGPADA KOTA TANGERANG - Nur Azizah; Dwi Oktaviani; Windy Lia Safitri (CCIT Journal, 2015)
In planning the procurement of goods and services the government city of Tangerang, will be compiled in a budget plan regional work units (RKA-on education) allocated from the Budget Revenue and Expenditure for Fiscal Year 2013, the compilation takes into account Standard Price of Goods. The problem faced now is the drafting, discussion and Standard Storage Unit Price still use the document to be signed by the Drafting Team and the Mayor of Tangerang as authorizing the Mayor's decision, and the data is stored in a file on Ms. Excel 2007. This proved to be less effective and time efficiency, especially when searching required by the standard price of sector departments. And waste paper for printing the books for sector departments in the form of a report each fiscal year. To overcome these problems were created Standards Information System using the web-based Goods Price CodeIgniter 2.0 framework and data storage using MySQL. With the construction of this system is expected to boost the quality of information transmission standard price of goods in the city of Tangerang.